Taking Up Faith: Ethical Methods for Studying Writing in Religious Contexts. (October 2015) - Pavia, Catherine Matthews
Greater attention to methods and methodologies when studying writing in religious contexts is needed to help researchers navigate ethical issues specific to faith communities and religious practices; to improve knowledge regarding the relationships among writing, religion, and faith; and to encourage respect for religious and nonreligious beliefs. To that end, I present findings from a study based on interviews of 14 scholars who have published results from their empirical studies on writing and religion or faith. Specifically, interview data show, first, researchers' religious positionalities acting as terministic screens and promoting identification with participants, and, second, researchers' efforts to fairly represent participants' beliefs and the methods they use to do so. The article also offers a heuristic, based on findings from the interviews, for maintaining a reflective position when conducting research on writing and religious contexts.